Powers of Early Childhood Education Teacher Against Expectations of XXI Century - Czerwonka, Dagna (Nauczyciel wczesnej edukacji: Rozwijanie kompetencji zawodowych, 2016)
Stage early childhood education is an important stage of life of every young person. It is extremely difficult and responsible, because it requires the teacher’s knowledge, creative engagement, to perceive and anticipate needs, problems and abilities of each pupil. It is safe to say that the biggest changes and modifications in the Polish education system are primarily tasks, activities and the competence of the teacher. There is a strong need to look for a new era teacher who is able to meet the new challenges of education. What are the expectations of the modern early childhood education teacher? What should have competence for the modern educator? The author of this article will try to answer.